EVALUASI PROGRAM JAMINAN PERSALINAN DI PUSKESMAS BONTOBAHARI KABUPATEN BULUKUMBA (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to find out the evaluation of the maternity insurance program at the Bontobahari Health Center, Bulukumba Regency. The research method used descriptive qualitative. Based on the results of the study, it was shown that the guarantee of delivery at the Bontobahari Health Center had not been achieved optimally due to several inhibiting factors. The first inhibiting factor was the provision of facilities and infrastructure where the existing service support facilities at the Bontobahari Health Center were not adequate, for example patient parking facilities, comfortable waiting rooms for the community and patients, adequate room lighting, and much more. Second, there was a lack of communication between the parties involved where the government was lacking in socializing the Jampersal program and explaining clearly  in the maternity insurance program ( Jampersal service process)